Effects of rare earth element Gd on microstructure, thermodynamic parameters, mechanical, and shape recovery properties of CuAlTa alloys - Ercan, Ercan; Al, Emre Bahadir; Dagdelen, Fethi (Springer, 2023)
The microstructure, thermodynamic parameters, mechanical properties, and shape recovery properties of alloys consisting of Cu83.5-xAl13.5Ta3Gdx (x = 0, 0.5, 1 mass%) alloy were investigated. Results showed that the addition of Gd to the alloys affects the martensite phase structure, creating new phases resembling snow crystals. An increase in Gd led to the formation of Al3GdCu intermetallic phase structures. Furthermore, the study found that while Gd influenced the thermodynamic parameters, it did not impact the high-temperature shape memory feature. Through microstructure analysis, it was determined that the addition of Gd to the alloy resulted in thinning of the martensite and austenite phase structures, leading to a reduction in grain size and changes in crystallite size. The higher microhardness observed in the EE1 alloy was attributed to its denser beta-Ta phase structures compared to other alloys.
Keywords: Rare earth elements; Shape recovery properties; Martensite phase; Microstructure